2016
DOI: 10.1186/s13058-016-0787-0
|View full text |Cite
|
Sign up to set email alerts
|

Mammographic density assessed on paired raw and processed digital images and on paired screen-film and digital images across three mammography systems

Abstract: BackgroundInter-women and intra-women comparisons of mammographic density (MD) are needed in research, clinical and screening applications; however, MD measurements are influenced by mammography modality (screen film/digital) and digital image format (raw/processed). We aimed to examine differences in MD assessed on these image types.MethodsWe obtained 1294 pairs of images saved in both raw and processed formats from Hologic and General Electric (GE) direct digital systems and a Fuji computed radiography (CR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Volumetric methods utilize the physics of x‐ray attenuations in breast tissue to estimate how much dense fibroglandular tissue exists in each given x‐ray path length. The area‐based PD is the most validated measure and researchers are actively using this measure, as indicated in recent studies . Among the above algorithms, Cumulus, a semi‐automatic area‐based method for estimating PD from the University of Toronto, is considered the gold standard for segmenting dense areas of the breast and estimating PD from given mammograms.…”
Section: Introductionmentioning
confidence: 99%
“…Volumetric methods utilize the physics of x‐ray attenuations in breast tissue to estimate how much dense fibroglandular tissue exists in each given x‐ray path length. The area‐based PD is the most validated measure and researchers are actively using this measure, as indicated in recent studies . Among the above algorithms, Cumulus, a semi‐automatic area‐based method for estimating PD from the University of Toronto, is considered the gold standard for segmenting dense areas of the breast and estimating PD from given mammograms.…”
Section: Introductionmentioning
confidence: 99%
“…unlikely to influence their intention to participate in screening). Finally, the processing applied to FFDM images to improve detection is known to alter the appearance of MD during measurement using the Cumulus software [35]. Despite reduced power to detect associations due to stratification by film/FFDM status, overall interpretation of the results was similar for both datasets; Aboriginal women have, on average, more NDA and lower amounts of MD than other Non-Aboriginal women.…”
Section: Discussionmentioning
confidence: 99%
“…[22, 34] Further, studies which have assessed percent MD from digital mammograms and risk of breast cancer demonstrated that MD as assessed from digital mammography was valid and had similar association with breast cancer risk as was seen with film mammograms. [35] Additionally, recently published work from the International Pooling Project of Mammographic Density observed that in 128 paired images “MD differences between screen-film [mammograms] and processed digital [mammograms] on the subsequent screening round were consistent with expected time-related MD declines.”[36] Another limitation is that NHS and NHSII participants are predominantly Caucasian and are more similar to each other in various characteristics (e.g., education) than the general population, potentially limiting generalizability. Additional validation of the prediction model would be useful, especially in diverse populations.…”
Section: Discussionmentioning
confidence: 99%